Smartphone apps as a technological innovation for weight reduction: a systematic review & meta-analysis - Azmawati Mohammed Nawi,; Muhammad Faiz Mohd Ishak,; Noor Hazmi Noor Hassim,; Safirah Jaan Jaafari,; Qistina Mohd Ghazali,; Mohd Rohaizat Hassan,; Norfazilah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Purpose - The new technological innovation can have a vast potential for interventions to help weight loss and combat obesity. The current meta-analysis aimed to compare the effectiveness of smartphone applications (apps) with other methods for promoting weight loss. Design/methodology - PubMed, Ovid and Science Direct were searched from 2014 all-inclusive up to May 2019 for relevant studies that assessed any smartphone/mobile phone app intervention with anthropometric measurement. Statistical analysis performed to examine mean difference (95% CI) of body weight, body mass index and waist circumference. Six articles were included for meta-analysis. Findings - According to the results, compared with conventional or other interventions, smartphone app interventions showed statistically non-significant decreases in body weight, body mass index and waist circumference. Intervention through smartphone apps alone does not produce substantial evidence of weight loss, even though they might be useful for specific groups. There remain prospects to explore regarding the use of smartphone apps in combination with other approaches to aid and promote weight loss, as smartphone use has been proven to influence health-related behavioral modification.